The impact of data selection and fitting on SAR estimation for magnetic nanoparticle heating. (15th December 2020) - Ring, Hattie L.; Sharma, Anirudh; Ivkov, Robert; Bischof, John C.
Abstract: Background: Magnetic fluid heating has great potential in the fields of thermal medicine and cryopreservation. However, variations among experimental parameters, analysis methods and experimental uncertainty make quantitative comparisons of results among laboratories difficult. Herein, we focus on the impact of calculating the specific absorption rate (SAR) using Time-Rise and Box-Lucas fitting. Time-Rise assumes adiabatic conditions, which is experimentally unachievable, but can be reasonably assumed (quasi-adiabatic) only for specific and limited evaluation times when heat loss is negligible compared to measured heating rate. Box-Lucas, on the other hand, accounts for heat losses but requires longer heating. Methods: Through retrospective analysis of data obtained from two laboratories, we demonstrate measurement time is a critical parameter to consider when calculating SAR. Volumetric SAR were calculated using the two methods and compared across multiple iron-oxide nanoparticles. Results: We observed the lowest volumetric SAR variation from both fitting methods between 1–10 W/mL, indicating an ideal SAR range for heating measurements. Furthermore, our analysis demonstrates that poorly chosen fitting method can generate reproducible but inaccurate SAR. Conclusion: We provide recommendations to select measurement time for data analysis with either Modified Time-Rise or Box-Lucas method, and suggestions to enhance experimental precision and accuracy when conducting heating experiments.